THE EFFECT OF PROFESSIONALISM, AUDIT EXPERIENCE ON AUDIT QUALITY WITH TIME BUDGET PRESSURE AS A MODERATOR AT THE INSPECTORATE OF WEST KALIMANTAN PROVINCE - Riyadi, Bernardus; Yantiana, Nella; Rusliyawati , Rusliyawati (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This study aims to test and analyze the effect of professionalism and auditor experience on audit quality with time budget pressure as a moderating variable. The research method uses explanatory research; the population of this study is at the Inspectorate of West Kalimantan Province with the target of the State Civil Apparatus (ASN), with the total population in this study being 51 Respondents. The data analysis technique used is SEM-PLS with WarpPLS 8.0 software. The results showed that professionalism and auditor experience positively affect audit quality, while time budget pressure weakens the influence of professionalism and auditor experience on audit quality. The coefficient of determination of Audit Quality (Y) is 0.350, which means that the variation in changes in audit quality can be explained by the variables of professionalism and audit experience by 35%. In comparison, the remaining 65% is explained by other variables not included in this study.